2017
DOI: 10.1158/1055-9965.epi-17-0293
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin, Glucose, Indices of Insulin Resistance, and Risk of Lung Cancer

Abstract: Background Although insulin may increase risk of some cancers, few studies have examined fasting serum insulin and lung cancer risk. Methods We examined serum insulin, glucose, and indices of insulin resistance (insulin:glucose molar ratio and homeostasis model assessment of insulin resistance [HOMA-IR]) and lung cancer risk using a case-cohort study within the Alpha-Tocopherol, Beta-Carotene Cancer Prevention Studyof Finnish men. 196 cases and 395 subcohort members were included. Insulin and glucose were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 34 publications
1
54
1
Order By: Relevance
“…Argirion et al. found that higher fasting serum insulin concentrations, as well as the presence of IR were associated with an elevated risk of lung cancer development ( 11 ). IR may mediate cancer-related functions fairly distinct from its obesity-related aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Argirion et al. found that higher fasting serum insulin concentrations, as well as the presence of IR were associated with an elevated risk of lung cancer development ( 11 ). IR may mediate cancer-related functions fairly distinct from its obesity-related aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the relationship between insulin resistance and the development of cancers such as prostate cancer and thyroid cancer ( 9 , 10 ). However, studies remain conflicting regarding the relationship between lung cancer and insulin resistance, as positive or invalid association has been reported ( 11 , 12 ). Assessment of the homeostasis model of insulin resistance based on fasting glucose and insulin levels (HOMA-IR) is a widely used surrogate indicator of IR in clinical practice ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Growing reports have suggested that insulin may increase the risk of certain cancers, such as prostate, rectal, breast and pancreatic cancers ( Hsing et al., 2001 ; Goodwin et al., 2002 ; Stolzenberg-Solomon et al., 2005 ; Limburg et al., 2006 ; Albanes et al., 2009 ). A case cohort study in 2017 found that higher insulin levels and insulin resistance may increase the risk of lung cancer ( Argirion et al., 2017 ). In addition, Hayakawa et al.…”
Section: Discussionmentioning
confidence: 99%
“…IR was related to increased lung cancer risk [ 41 ], and insulin may also influence obesity-mediated tumors such as renal cancer and ovarian tumor [ 42 , 43 ], but the relationship between insulin and ESCC growth had not been examined in the study. The novel findings of this study that serum visfatin and leptin were positively related to xenograft tumor growth were consistent with the notion that adipokines and other growth factors secreted on the background of obesity may prompt cancer cell survival and tumor growth.…”
Section: Discussionmentioning
confidence: 99%